TTK (threonine tyrosine kinase) regulates the malignant behaviors of cancer cells and is regulated by microRNA-582-5p in ovarian cancer. Issue 1 (1st January 2021) - Lu, Na; Ren, Lixin
ABSTRACT: There is growing evidence that threonine tyrosine kinase (TTK) dysregulation is linked to the progression of multiple malignancies. Nonetheless, the role of TTK in ovarian cancer (OC) remains unclear. The GEO2R method was employed to screen out the mRNAs that were abnormally expressed between OC tissues and normal ovarian tissues using three datasets from the Gene Expression Omnibus (GEO) database: GSE14407, GSE18520, and GSE36668. Moreover, the Kaplan–Meier plotter was utilized to investigate the association between TTK expression and OC patients' prognosis. Furthermore, quantitative real-time PCR (qRT-PCR) was applied to examine miR-582-5p expression and TTK mRNA expression in OC tissues and cells. Additionally, immunohistochemistry (IHC) experiment and Western blot were executed to examine TTK protein expression in OC tissues and cells, respectively. In addition, Cell Counting Kit-8 (CCK-8), transwell, and flow-cytometry experiments were performed to examine the multiplication, migration, and apoptosis of OC cells, respectively. In addition, dual-luciferase reporter gene tests were executed to validate the targeting relationship between miR-582-5p and TTK. We demonstrated that TTK expression was up-regulated in OC tissues and cells, and its overexpression was found to be associated with an adverse prognosis in OC patients. TTK overexpression enhanced OC cell multiplication and migration, and repressed apoptosis. Mechanistically, TTK was a downstream target of miR-582-5p. Furthermore, miR-582-5p overexpression impeded OC cell multiplication and migration, while TTK overexpression reversed this phenomenon. These data suggest that miR-582-5p and TTK are promising targets for OC diagnosis and therapy.